Wartość dialogu międzykulturowego w przezwyciężaniu konfliktów na pograniczach kulturowych (Zakład Pedagogiki Społecznej Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The starting proposal is the assumption that intercultural dialogue is a product of a difficult process of balancing emotions, damping down and curbing negative emotions, learning to progress from reaction to interaction with the Others. Lack of intercultural dialogue can trigger negative emotions towards the Others, effectively forming a culture of fear and neoprimitive thinking and awareness. ;
Keywords: multiculturalism; cultural education